Electromagnetic wave absorbing material and preparation method thereof
The core-shell composite structure of MoS2 coated hollow Cu9S5 cubes was prepared by hydrothermal method, which solved the problem of complex and high cost of preparation of 1T-MoS2 materials, achieved efficient electromagnetic wave absorption performance, avoided MoS2 agglomeration, and significantly improved electromagnetic wave absorption effect .
Patent Information
- Application Number
- CN202310739975.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-21
AI Technical Summary
The existing 1T-MoS2 material has complex preparation methods, high cost and poor electromagnetic wave absorption performance, making it difficult to provide a material with low cost, simple preparation method and excellent electromagnetic wave absorption performance.
The hydrothermal method was used to mix Cu2O powder, ammonium molybdate and thiourea to prepare a core-shell composite structure with MoS2 coated with hollow Cu9S5 cubes. NH4+ was inserted in the acid environment to form an electromagnetic wave absorbing material with a high proportion of 1-T phase. The transition agglomeration problem of MoS2 is avoided and loaded on the surface of Cu2-xS hollow box through the self-template growth mechanism of MoS2 nanosheets.
It is realized that the conductive network is formed at a lower mass filling concentration, with excellent electromagnetic wave absorption characteristics, significantly improving the electromagnetic wave absorption performance, and the preparation process is simple and low cost.
Smart Images

Figure CN119181982A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to an electromagnetic wave absorbing material and a preparation method thereof. Background Art
[0002] Graphene is considered to be a typical two-dimensional layered material. Due to its excellent physical and chemical properties, it is an ideal lightweight electromagnetic wave (EMW) absorber. Although the design of different types of graphene-based composite electromagnetic wave absorbers is quite mature, its high price limits its application. It is urgent to develop practical absorbers to solve the increasingly severe electromagnetic pollution problem. Among the alternative two-dimensional material candidates, as a typical representative of transition metal sulfides (TMDs), the layered structure of MoS2 has been widely studied due to its many interesting properties. In 2015, Ning et al. first reported the electromagnetic wave absorption properties of MoS2 nanosheets prepared by hydrothermal method. Subsequently, some MoS2-based composite absorbers have been reported, including composites of MoS2 and semiconductor materials, conductive materials and ferromagnetic materials. The good dielectric loss capacity and impedance matching characteristics make MoS2 regarded as a new type of electromagnetic wave absorber.
[0003] Due to the different coordination modes between transition metal elements and chalcogenides, TMDs usually exist in multiple forms. For MoS2, it usually presents two phases in structure, namely the 2H phase with hexagonal coordination and the 1T phase with octahedral coordination, which depends on the positions of the six S atoms around the Mo atom. The crystal phase structure of the material plays a vital role in determining its physical, chemical and electronic properties, so its intrinsic properties can be adjusted by manipulating the crystal structure of MoS2. The active sites of 2H-MoS2 are only at the edges, so the electron transport properties are poor, which limits its application in catalysis and electrochemistry. Fortunately, these problems can be solved by converting it into 1T phase. 1T-MoS2 has excellent electronic, optical and mechanical properties. By precisely tailoring the size of 1T-MoS2 nanosheets and rationally combining 1T-MoS2 nanosheets and other functional materials, new interface materials with unique crystal phase structures can be obtained. Considering the superior properties of the 1T phase, phase regulation of MoS2 is expected to be an effective method to improve the electromagnetic wave absorption performance.
[0004] Due to the metastability of 1T-MoS2, it is generally difficult to obtain in nature. Therefore, many studies are devoted to the technology of directional regulation of 2H-MoS2 to generate 1T-MoS2, including element doping, temperature regulation, pressure regulation, stress regulation, plasma / electron bombardment induction, gas molecule induction, etc. Although great results have been achieved, there are problems such as high cost and complicated operation steps in many methods used to improve the proportion of 1T phase in MoS2. In addition, due to the existence of van der Waals force, layered MoS2 is easy to agglomerate and stack, resulting in a large dead volume, which will limit the response of electromagnetic waves.
[0005] Therefore, how to provide an electromagnetic wave absorbing material with low cost, simple preparation method and excellent electromagnetic wave absorbing performance has become a problem that technical personnel in this field need to solve urgently. Summary of the invention
[0006] In view of this, the present invention provides an electromagnetic wave absorbing material and a preparation method thereof, the purpose of which is to solve the technical problems that the preparation method of the existing 1T-MoS2 material is complex, costly and has poor electromagnetic wave absorption performance.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention provides a method for preparing an electromagnetic wave absorbing material, comprising the following steps:
[0009] The electromagnetic wave absorbing material is obtained by mixing Cu2O powder, ammonium molybdate, thiourea and water and reacting them.
[0010] Furthermore, the molar ratio of the Cu2O powder to ammonium molybdate is 3-4:0.25-1.
[0011] Furthermore, the Mo / S molar ratio of the ammonium molybdate and thiourea is 1:2-8.
[0012] Furthermore, the molar volume ratio of the ammonium molybdate to water is 0.25-1 mmol: 100-200 mL.
[0013] Furthermore, the reaction temperature is 160-240° C., and the reaction time is 20-30 hours.
[0014] The present invention also provides an electromagnetic wave absorbing material prepared by the above preparation method.
[0015] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0016] The electromagnetic wave absorbing material prepared by the present invention is a core-shell composite structure of MoS2 coated hollow Cu9S5 cubes prepared by a simple hydrothermal method. In an acid environment, a large amount of NH4 +Inserted into the MoS2 interlayer, it has a high 1-T phase ratio. In addition, the self-template growth mechanism of MoS2 nanosheets is applied to the surface loading of Cu2-xS hollow boxes to avoid the problem of MoS2 transition agglomeration;
[0017] Due to the excellent properties of the hollow structure, a conductive network can be formed at a relatively low mass filling concentration. In addition, multiple dielectric loss mechanisms such as dipole polarization and interface polarization make the electromagnetic wave absorbing material prepared by the present invention have excellent electromagnetic wave absorption properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a crystal structure and morphology information diagram of the Cu2O powder used in Examples 1 to 3 of the present invention;
[0019] Figure 2 Cu 2-x S@MoS2-1, Cu 2-x S@MoS2-2 and Cu 2-x Microscopic morphology of S@MoS2-3;
[0020] Figure 3 Cu 2-x Schematic diagram of the synthesis process of S@1T-MoS2 hollow microbox;
[0021] Figure 4 a, b, c, d are Cu 2-x XRD spectrum, XPS spectrum, Cu2p spectrum and Mo3d spectrum of S@MoS2;
[0022] Figure 5 The composition ratio of Cu9S5 and MoS2 in the products of Examples 1 to 3 is shown in FIG.
[0023] Figure 6 Cu 2-x Complex dielectric constant diagram of S@MoS2 sample with a filling ratio of 40wt%;
[0024] Figure 7 Cu 2-x Reflection loss evaluation diagram of S@MoS2 sample. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing an electromagnetic wave absorbing material, comprising the following steps:
[0026] The electromagnetic wave absorbing material is obtained by mixing Cu2O powder, ammonium molybdate, thiourea and water and reacting them.
[0027] In the present invention, the molar ratio of the Cu2O powder to ammonium molybdate is 3-4:0.25-1, preferably 3.2-3.6:0.4-0.8, and more preferably 3.5:0.5-0.6.
[0028] In the present invention, the Mo / S molar ratio of the ammonium molybdate and thiourea is 1:2-8, preferably 1:4-6.
[0029] In the present invention, the molar volume ratio of ammonium molybdate to water is 0.25-1 mmol: 100-200 mL, preferably 0.4-0.8 mmol: 120-180 mL, and more preferably 0.5-0.6 mmol: 140-160 mL.
[0030] In the present invention, the reaction temperature is 160-240° C., preferably 200-220° C.; the reaction time is 20-30 h, preferably 24-26 h.
[0031] The present invention also provides an electromagnetic wave absorbing material prepared by the above preparation method.
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] 3.5mmol Cu2O powder, 0.25mmol ammonium molybdate and thiourea were uniformly dissolved in 100mL deionized water to obtain a mixed solution with an element ratio of Mo:S=1:4. The mixed solution was then reacted at 200°C for 24 hours. After the reaction was completed, it was collected by suction filtration, washed with deionized water three times, and vacuum dried at 60°C. The obtained product was recorded as Cu 2-x S@MoS2-1.
[0035] Example 2
[0036] 3.5mmol Cu2O powder, 0.5mmol ammonium molybdate and thiourea were uniformly dissolved in 100mL deionized water to obtain a mixed solution with an element ratio of Mo:S=1:4. The mixed solution was then reacted at 200°C for 24 hours. After the reaction was completed, it was collected by suction filtration, washed with deionized water three times, and vacuum dried at 60°C. The obtained product was recorded as Cu 2-x S@MoS2-2.
[0037] Example 3
[0038] 3.5mmolCu2O powder, 1mmol ammonium molybdate and thiourea were uniformly dissolved in 100mL deionized water to obtain a mixed solution with an element ratio of Mo:S=1:4. The mixed solution was then reacted at 200℃ for 24 hours. After the reaction was completed, it was collected by suction filtration, washed with deionized water for 3 times, and vacuum dried at 60℃. The obtained product was recorded as Cu 2-x S@MoS2-3.
[0039] Figure 1 The figure is a crystal structure and morphology information diagram of the Cu2O powder used in Examples 1 to 3 of the present invention. Figure 1 It can be obtained that the Cu2O powder has uniform particle size, smooth surface and good dispersibility, and its average size is about 1um.
[0040] Figure 2 Cu 2-x S@MoS2-1, Cu 2-x S@MoS2-2 and Cu 2-x The microscopic morphology of S@MoS2-3 shows that Cu 2-x S@1T-MoS2 presents a hollow structure. When the dosage of ammonium molybdate and thiourea is low, some broken box particles can be observed, and the surface is slightly rough. As the dosage of ammonium molybdate and thiourea increases, the surface gradually becomes flat, and the breakage rate of the box particles decreases, indicating that the MoS2 is evenly covered ( Figure 2 a1-c1). Cu was observed by TEM images. 2-x Shell state of S@1T-MoS2 hollow microbox ( Figure 2 a2-c2), it can be observed that the MoS2 nanosheets gradually thicken and grow with the increase of the amount of ammonium molybdate & thiourea, from the initial attachment growth to the final vertical growth on the surface of the box particles. 2-x The size of the S@MoS2-3 microbox structure shrinks significantly ( Figure 2 a3-c3), which is related to the surface sulfidation of Cu2O and NH4 + It is related to the synergistic effect on the etching of Cu2O.
[0041] Figure 3 Cu 2-x Schematic diagram of the synthesis process of S@1T-MoS2 hollow microbox. Since the electronegativity of O is stronger than that of S, the O element in Cu2O is very easy to be replaced by S. In addition, the NH4 + It can react with Cu2O to form a copper-ammine complex, which is the etching process. The S element in the system and NH4 + If the sulfurization process is dominant, a solid Cu 2-xS cubes; if the etching process dominates, the cubes will completely dissociate into fragments. Therefore, the formation of a perfect hollow structure is the result of the competition between the sulfurization process and the etching process, which eventually tends to an equilibrium state. When the concentrations of ammonium molybdate and thiourea are low, the Cu 2-x S@MoS2-1 and Cu 2-x The morphology and size of S@MoS2-2 are similar to those of the original Cu2O cubes, indicating that the sulfurization process takes precedence over the etching process. After the sulfurization reaction on the Cu2O surface, the residual Cu2O inside is immediately oxidized by NH4 + When the concentration of ammonium molybdate and thiourea is high, the Cu 2-x The size of S@MoS2-3 is significantly reduced, and the internal hollow part is transformed from a cube to a rounded cube, indicating that the etching process at this time occurs before the sulfurization process, and the Cu2O surface sulfurization is completed in the subsequent etching process.
[0042] Figure 4 a, b, c, d are Cu 2-x XRD spectrum, XPS spectrum, Cu2p spectrum and Mo3d spectrum of S@MoS2. Figure 4 As shown in a, the diffraction peaks of the prepared sample at 27.8°, 29.2°, 32.0°, 41.6° and 54.4° correspond to the (751), (911), (1000), (1081), (10100) and (1641) crystal planes of the PDF#09-0064 standard card, respectively, indicating that the obtained product is mainly cubic Cu9S5. 2-x The diffraction peak of S@MoS2-1 shows weak noise, which is caused by insufficient crystallinity. As the concentration of ammonium molybdate and thiourea increases, the diffraction peak becomes sharper and the crystallinity of the sample increases. 2-x S@MoS2-1 and Cu 2-x The reason why no diffraction peak of MoS2 is observed in S@MoS2-2 is due to the low content of MoS2. 2-x S@MoS2-3 shows a sharp diffraction peak (red dot) at 9.6°, representing 1T-MoS2. XPS spectra are used to analyze the elemental composition of the samples. Figure 4 b shows the total spectrum of the three samples, where the presence of Cu, O, N, C, Mo, and S elements can be observed. As the concentrations of ammonium molybdate and thiourea increase, the relative signal intensity of the Mo3d orbital and the S2p orbital increases. The Cu2p spectrum is used to further analyze the chemical valence state of the Cu element ( Figure 4 c), where the two main peaks at 932.3 eV and 952.0 eV belong to Cu2p 3 / 2 and Cu2p1 / 2 , corresponding to Cu + And no independent satellite peaks were observed at 942.6eV and 962.2eV, indicating that there is almost no Cu in the product 2+ The above proves that the chemical valence state of Cu element is Cu + This is consistent with the valence characteristics of the product Cu9S5. 2-x The proportion of 1T phase in S@1T-MoS2 was calculated using the integral of Mo3d ( Figure 4 d) The 1T phase in Cu2-xS@MoS2-1 accounts for 79.2%, slightly lower than that of pure NH4 + -MoS2, which is the copper-ammine complexation that consumes part of the NH4 + Caused by.
[0043] In order to calculate the composition ratio of Cu9S5 and MoS2 in the products of Examples 1 to 3, EDS-mapping elements were used to quantitatively analyze Mo, N, Cu, and S. Figure 5 The colored dots in the figure confirm the uniformity of the distribution of Mo, N, Cu, and S elements. The atomic ratios of Cu, Mo, and S are consistent with the material combination of Cu9S5+MoS2. 2-x S@MoS2-1 and Cu 2-x The content of Mo in S@MoS2-2 is low, which is the main reason why no MoS2 diffraction peak can be observed in the XRD pattern. When the concentration of ammonium molybdate and thiourea continues to increase, the loading amount of MoS2 on Cu9S5 continues to increase until Cu 2-x In S@MoS2-3, the ratio of Cu atoms to Mo atoms is close to 1:1, indicating that there is more MoS2 loading on Cu9S5.
[0044] Performance Testing
[0045] Figure 6 ab is Cu 2-x The complex dielectric constant of the S@MoS2 sample with a filling ratio of 40wt% can be observed to be significantly higher than that of NH4 + -MoS2-40wt%, indicating that these hollow core-shell particles can successfully form a conductive network at a lower filling ratio. Figure 6 As can be seen in a, with the increase of ammonium molybdate and thiourea concentrations, Cu 2-xThe increase in the proportion of MoS2 in S@MoS2 is helpful to reduce the ε′ value. The reduction of the ε′ value can improve the impedance matching between the medium and the air, allowing more electromagnetic waves to enter the medium. However, at frequencies above 6 GHz, it can be observed that the ε″ value decreases with the increase in MoS2 loading. Although theoretically the 1T phase of MoS2 has a very high conductivity value, the increase in MoS2 loading will lead to a significant thickening of the shell of the core-shell particles and a decrease in the degree of hollowing, and the volume concentration at the same filling mass will decrease, thereby weakening the dielectric loss capacity of the product.
[0046] Cu 2-x The reflection loss of S@MoS2 was evaluated and the results are shown in Figure 7 As shown in ac, Cu 2-x The electromagnetic wave absorption performance of S@MoS2 is significantly better than that of NH4 + -MoS2. Generally speaking, -10dB R L The value is taken as the qualified electromagnetic wave absorption threshold, R L The frequency region below -10 dB is called the effective absorption band (EAB), which means that at least 90% of the electromagnetic waves are lost. Figure 7 df detailed statistics of the minimum R in the range of 0 to 5 mm L The values and their corresponding EAB show that with the increase of MoS2 loading, the absorption of electromagnetic waves by the samples shows an enhanced trend. 2-x S@MoS2-1 R at 1.9mm L min can reach -31dB, and the effective frequency range is 10.4GHz~13.4GHz; Cu 2-x S@MoS2-2 R at 3mm L min can reach -44.6dB, and the effective frequency range is 6.6GHz~9.6GHz; Cu 2-x S@MoS2-3 R at 2.1mm L min can reach -52.2dB, and the effective frequency range is 11.9GHz~16.6GHz. Therefore, no matter which sample, its R L min is far beyond the -10dB absorption standard. 2-x S@MoS2-3 has the most superior electromagnetic wave absorption performance because it has both wide bandwidth and strong absorption at 2.1 mm.
[0047] In summary, the core-shell composite structure of MoS2 coated hollow Cu9S5 cubes prepared by a simple hydrothermal method in the present invention is a large amount of NH4 +Inserted into the MoS2 interlayer, it has a high 1-T phase ratio. In addition, the self-template growth mechanism of MoS2 nanosheets is applied to Cu 2-x The surface loading of the S hollow box avoids the problem of transitional agglomeration of MoS2. Due to the excellent characteristics of the hollow structure, a conductive network can be formed at a lower mass filling concentration. In addition, multiple dielectric loss mechanisms such as dipole polarization and interface polarization are also possible. 2-x S@MoS2 has excellent electromagnetic wave absorption properties. As the MoS2 loading increases, the impedance characteristics of the sample continue to be optimized. 2-x S@MoS2-3 exhibits enhanced electromagnetic wave absorption performance, achieving a RL of -52.2 dB and an EAB of about 4.7 GHz at 2.1 mm.
[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an electromagnetic wave absorbing material, characterized in that: The following steps are involved: The electromagnetic wave absorbing material is obtained by mixing Cu2O powder, ammonium molybdate, thiourea and water and reacting them; The molar ratio of the Cu2O powder to ammonium molybdate is 3-4:0.25-1.
2. The preparation method according to claim 1, characterized in that: The Mo / S molar ratio of the ammonium molybdate and thiourea is 1:2-8.
3. The preparation method according to claim 2, characterized in that: The molar volume ratio of the ammonium molybdate to water is 0.25-1 mmol: 100-200 mL.
4. The preparation method according to claim 1 or 3, characterized in that: The reaction temperature is 160-240° C., and the reaction time is 20-30 hours.
5. The electromagnetic wave absorbing material prepared by the preparation method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Cu2O / multi-walled carbon nanotubes (MWCNTs) composite material, preparation method thereof and electromagnetic absorption application
CN107454815A
MoS2@Cu2S@ copper foam composite nanometer material and preparation method and application thereof
CN108950585A
High-performance wave-absorbing material core-shell structure CoxFe3-xO4@MoS2 nano-composite and synthesis method thereof
CN109943285A
Cu9S5 / C composite material, and preparation method and application thereof
CN112996375A
Three-dimensional porous 1T-MoS2 nanosheet / polyaniline nanocomposite and preparation method and application thereof
CN114456376A
